Avaliação de Saúde Mental em Gestantes - Poliana Patrício Aliane; Telmo Mota Ronzani; Cristiane Schumann Silva; Gabriel Resgala Silva; Daniele Batista Miranda; Priscila Ferreira de Oliveira; Aline Fajardo Mendes; Erikson Felipe Furtado (Gerais, 2008)
The pregnancy and puerperium period is a phase of increased incidence of mental disorders in women,requiring special attention to ensure the maintenance of their well-being and prevention of future cognitive andemotional difficulties for their child. The present research aimed at verifying, through a pilot study, theincidence of psychiatric symptoms and alcohol use among pregnant women attending the public health systemof Juiz de Fora, MG. 33 pregnant women of 3 health units had been interviewed using the instruments QMPAand MINI/DSM-IV. It was verified that 54.5% of the women interviewed presented seven or more psychiatricsymptoms described in the QMPA, with a prominence of the anxiety subscale. Amongst the results of theMINI/DSM-IV, the high incidence of current Agoraphobia can be highlighted (37.7%), Agoraphobia withoutPanic Disorder (33.3%), Psychotic Syndrome (25.0%), Bigger Depressive Episode Current (24.2%) andGeneralized Anxiety Disorder (15.2%). The high incidence of psychiatric disorders found indicated thenecessity of detailed clinical inquiries for the evaluation of the mental health of pregnant women and possiblereferal for treatment. The pilot study constitutes an important stage of the research, since the preliminary results,as well as the initial methodological difficulties, will ensure the improvement of the final study.